2021
DOI: 10.3390/s21051734
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional Neural Network for Drowsiness Detection Using EEG Signals

Abstract: Drowsiness detection (DD) has become a relevant area of active research in biomedical signal processing. Recently, various deep learning (DL) researches based on the EEG signals have been proposed to detect fatigue conditions. The research presented in this paper proposes an EEG classification system for DD based on DL networks. However, the proposed DD system is mainly realized into two procedures; (i) data acquisition and (ii) model analysis. For the data acquisition procedure, two key steps are considered, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(28 citation statements)
references
References 113 publications
1
27
0
Order By: Relevance
“…The selection of layers to be learned versus those to be reused and the initialization of weights are some fundamental things to be learned from experimenting with the target dataset. Approaches such as [ 31 , 36 ] use deep learning features but are preceded by a pipeline of preprocessing tasks. Similarly, in [ 37 ], the authors went through a laborious job of testing various combinations of channels on different architectures of CNN models before finding the one with the best performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The selection of layers to be learned versus those to be reused and the initialization of weights are some fundamental things to be learned from experimenting with the target dataset. Approaches such as [ 31 , 36 ] use deep learning features but are preceded by a pipeline of preprocessing tasks. Similarly, in [ 37 ], the authors went through a laborious job of testing various combinations of channels on different architectures of CNN models before finding the one with the best performance.…”
Section: Discussionmentioning
confidence: 99%
“…CNNs have been used in problems such as speech recognition, image classification, recommender systems, and text classification. More recently, CNNs have been shown to classify EEG brain signals for autism [ 46 ], epilepsy [ 46 , 47 , 48 , 49 ], seizure detection in children [ 50 ], schizophrenia [ 51 ], brain–computer interface (BCI) [ 52 ], alcoholism predisposition [ 21 , 37 ], drowsiness detection [ 36 , 53 ], and neurodegeneration and physiological aging [ 54 ] into normal and pathological groups of young and old people.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the authors used a publicly available database, they compared their deep learning (DL) approach with the other feature-based approaches, and they concluded that this approach resulted in at least 3% better results. Chaabene et al [174] used frequency-domain features for defining the ground truth. They used CNN with raw EEG signal from seven electrodes as input and achieved 90% drowsiness detection accuracy.…”
Section: Driver Drowsiness Detection Systemsmentioning
confidence: 99%
“…Recently, deep neural networks (DNNs) or convolutional neural networks (CNNs) have been widely applied to complicated signal processing, such as classification tasks and signal regression problems, due to their outstanding performances in nonlinear adaptability and feature extraction ( [1][2][3] and references therein) and are also extended to the distributed sensing systems (e.g., the object recognition using distributed micro-Doppler radars in [4] and the data driven digital healthcare applications [5][6][7]). In the distributed sensing systems, centralized training strategies may be adopted to train their common DNN or CNN modules by sharing their sensing data.…”
Section: Introductionmentioning
confidence: 99%